Strengthening biregional cooperation between Latin America and Asia-Pacific : the role of FEALAC (UN ECLAC SantiagoCL, 2013)
Examines the growing economic relations between Latin America and the Caribbean and the Asia-Pacific region.
Keywords: REGIONAL COOPERATION